Some Immunological Profiles in Women Practising DMPA Contraception in Malaria Endemic Area of Nnewi and Environs - H.I, Nwokolo; C.C, Onyenekwe; F.O, Emeremmdau; N.R, Ukibe (Archives of Clinical and Biomedical Research, 2017)
Many women are now enlisting in family planning clinics in a bid to spacing their children, but there are attendant complications often associated with the use. This study evaluated the effects of injectable Depot Medroxyprogesterone acetate (DMPA) contraceptive on some immunological profile in females attending family planning clinic in NAUTH, Nnewi. Fifty female DMPA contraceptive users were recruited into this study and were further subdivided into malaria positive and malaria negative groups before and three months after administration of DMPA. The study was a longitudinal cohort design and simple random sampling technique was used in the recruitment of subjects. Blood samples were collected from the subjects before and 3 months after administration of DMPA, Immunological profile (IgG (μg/ml), IgM (ng/ml) and IFN-γ (pg/ml) were done using Enzyme linked immunosorbent assay. Qualitative and quantitative determination of P. falciparium antigen parasite were done by rapid test device and Giemsa stained thick blood film for microscopic determination respectively. CD4+ T-cells (cell/μl) were analyzed by flow cytometry. The results showed that the mean±SD serum level of IgM (ng/ml) was significantly decreased 3 months after administration of DMPA (213.45±75.64) compared with value before DMPA administration (363.06±5.63) with or without malaria parasite infection (p=0.000).However, there was no significant difference in mean±SD serum levels of IgG, CD4+ T-cell, IFN-γ before and 3 months after administration of DMPA (p>0.05) there was no significant difference in mean±SD serum levels of IgG, IgM, IFN-γ, CD4+ T-cells between malaria positive and malaria negative subjects before and 3 months after administration of DMPA (p>0.05). Thus, the finding of the study suggests that DMPA did affect the IgM response, but no significant changes were observed in immunological parameters s